Phoenician Vengeance: Dido, Anna, and the Lore of the Numicus - Fratantuono, Lee (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
Scholarly attention has been paid to the depiction of the Carthaginian sisters Dido and Anna, particularly in Virgil’s fourth Aeneid. Close attention to the later portrayals of Anna in Ovid (Fasti 3) and Silius Italicus (Punica 8) reveals a portrayal of Dido’s sister as the unwitting agent of the fulfillment of the queen’s curse against Aeneas. The hitherto unappreciated connection between the festival of Anna Perenna and the date of the assassination of Gaius Julius Caesar may be seen in light of Dido’s curse on Aeneas and the Julian gens descended from his son Iulus.